Electro-stimulated drug release by methacrylated hyaluronic acid-based conductive hydrogel with enhanced mechanical properties - AYCAN, DİDEM; KARACA ALBAYRAK, FATMA; KOCA, ATIF; ALEMDAR YAYLA, NESLİHAN (My University, 2023)
© 2023 Elsevier B.V.Recently, the design of stimuli-responsive hydrogels for controlled drug delivery systems has been extensively investigated to meet therapeutic needs and optimize the release pattern of the drug. Being a natural polyelectrolyte, hyaluronic acid (HA) is excellent potential to generate new opportunities for electro-responsive drug carrier applications. In the current study, HA-based electroconductive hydrogel was developed as a novel smart drug carrier for anti-inflammatory drug release by the combination of in-situ and post polymerization mechanisms. HA was modified through methacrylation reaction to introduce photocrosslinkable groups into its structure and then reduced graphene oxide (rGO) was encapsulated into methacrylated HA (HA/MA) hydrogel by using the photopolymerization technique. In the post polymerization process, polyaniline (PANI) was incorporated/loaded into HA/MA-rGO polymeric network produced in previous step. The produced HA/MA-rGO-PANI hydrogel exhibited sufficient electrical conductivity providing the desirable electro-responsive ability for Ibuprofen (IBU) release. Furthermore, it has superior mechanical performance compared to pure (HA/MA) and rGO containing (HA/MA-rGO) hydrogels. IBU release from the hydrogel was successfully triggered by electrical stimulation and the cumulative drug release also enhanced by increasing of the applied voltage. These results highlighted that the novel HA/MA-rGO-PANI hydrogel could be a promising candidate for electrical-stimulated anti-inflammatory release systems in neural implant applications.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yapısal Biyoloji; Biyokimya; Moleküler Biyoloji; Structural Biology; Biochemistry; Molecular Biology; Electro-stimulated release; Hyaluronic acid; Ibuprofen